From literacy to norms: learning eco-andragogy through participatory environmental change in coastal Banyuwangi - Kholis Ridho; Sita Aisah Anggita; Ali Irfani (Jurnal Konseling dan Pendidikan, 2025)
The ecological transformation of coastal communities is achieved through the transmission of values, social interaction, education, participation, and institutionalization of collective norms. This study aims to analyze how the EcoRanger program, initiated by the NGO Greeneration Indonesia, can encourage changes in ecological behavior in the community of Pancer Hamlet, Banyuwangi. Using a phenomenological approach, this study explores residents' subjective experiences of the program intervention through in-depth interviews, participant observation, and documentation studies. The results indicate that the EcoRanger intervention successfully fostered ecological awareness through educational activities (Educamp and Envirosport), the provision of integrated waste management facilities (SEKOLA), and routine activities for residents and tourists (Weekly Beach Clean-Up). These changes are both material—visible in waste sorting and management practices—and immaterial, in the form of shifts in attitudes, active participation, and the formation of new, collectively maintained social norms. Religious values and local traditions, such as Petik Laut (Sea Sacred) and Baritan, contribute to the internalization of cleanliness messages as part of the community's faith and identity. EcoRanger acts as a social facilitator, filling the gap in the state's role in providing environmental services and public education. This study concludes that sustainable ecological transformation requires synergy between education, infrastructure, citizen participation, and the accommodation of local values. Theoretically, this research offers a novel contribution through the formulation of the concept of community ecoandragogy—an ecological education approach based on lived experience, critical reflection, and the institutionalization of social norms—that broadens the scope of ecopedagogy and can be replicated in other coastal areas.